Diversity-Oriented Synthesis of Novel Trihalomethyl-Containing Spirochromeno[3,4-a](thia)pyrrolizidines and Spirochromeno-[3,4-a]indolizidines by One-Pot, Three-Component [3+2]-Cycloaddition Reaction - Kutyashev, Igor B.; Sannikov, Maxim S.; Kochnev, Ivan A.; Barkov, Alexey Y.; Zimnitskiy, Nikolay S.; Korotaev, Vladislav Y.; Sosnovskikh, Vyacheslav Y. (SynOpen, 2021)
Regio- and stereoselective methods for the synthesis of 6′-trifluoro(trichloro)methyl substituted spiro[acenaphthylene-1,11′-chromeno[3,4-a](thia)pyrrolizidin]-2-ones and spiro[acenaphthylene-1,12′-chromeno[3,4-a]indolizidin]-2-ones have been developed based on the three-component reaction of 3-nitro-2-trifluoro(trichloro)methyl-2H-chromenes with azomethine ylides generated in situ from acenaphthenequinone and cyclic α-amino acids. The cycloaddition proceeds under mild conditions in ethanol or DMSO, and only endo-isomers of the products with cis-arrangement of nitro and trifluoromethyl groups are formed. The relative configuration of cycloadducts is reliably confirmed by X-ray diffraction analysis and by 2D NOESY spectroscopy.
Keywords: 3-nitro-2-trifluoro(trichloro)methyl-2H-chromenes; 1,3-dipolar cycloaddition; azomethine ylides; acenaphthenequinone; cyclic α-amino acids